1980
DOI: 10.1111/j.1540-8159.1980.tb04307.x
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Tricuspid Valve Malfunction Induced by a Pacemaker Lead: A Case Report and Review of the Literature

Abstract: A 23-year-old woman developed 3 degrees AV block with syncope. Insertion of a permanent pacemaker lead was followed by the onset of a persistent murmur in late systole preceded by single or multiple clicks. The murmur was best heard at the left sternal edge, grade 3-4/6 with two major frequencies (60-250 Hz), increased with inspiration and on assuming the erect posture. It was considered to be tricuspid in origin and related to interference of the tricuspid valve apparatus by the pacemaker lead resulting in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
6

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 21 publications
3
37
0
6
Order By: Relevance
“…Case reports in adults have noted severe TV regurgitation with an intracardiac lead across the valve (3,4). A retrospective study of 374 adults after transvenous pacemaker lead placement across the TV showed increased prevalence of significant TR when compared with age and sex-matched controls (5).…”
Section: Introductionmentioning
confidence: 99%
“…Case reports in adults have noted severe TV regurgitation with an intracardiac lead across the valve (3,4). A retrospective study of 374 adults after transvenous pacemaker lead placement across the TV showed increased prevalence of significant TR when compared with age and sex-matched controls (5).…”
Section: Introductionmentioning
confidence: 99%
“…Gibson еt al. впервые отметили важную закономерность, которая состоит в том, что частота встречаемости ТР возрастает прямо пропорционально частоте имплантаций искус-ственных водителей ритма [13].…”
Section: Discussionunclassified
“…Во-пер-вых, ее наличие в целом связано со снижением выживаемости больных, в крайних случаях мо-жет потребоваться хирургическая коррекция [8][9][10][11][12]. Во-вторых, учитывая ежегодно увеличи-вающееся количество имплантируемых ЭКС, можно ожидать значительного увеличения чис-ла подобных осложнений в ближайшем буду-щем [13,14]. С другой стороны, это ятрогенное осложнение, следовательно, оно может быть предотвращено или его последствия могут быть сведены к минимуму [15].…”
Section: Introductionunclassified
“…Gibson et al в 1980 г. [14]. Позже появи-лось определенное количество публикаций о появлении выраженной ТР после импланта-ции ААУ, и чаще всего они были представлены лишь описанием отдельных клинических случа-ев [15,16].…”
Section: имплантация антиаритмических устройств является методом выбоunclassified
“…Такая ситуация наблюдается при перфо-рации электродом одной из створок ТК, чаще всего задней [14], перфорации сухожильных хорд [25], перфорации папиллярных мышц ПЖ [14] или запутывании электрода в структурах ТК [9]. Такая ситуация достаточно редка, поэтому представлена в литературе описанием отдель-ных клинических случаев.…”
Section: имплантация антиаритмических устройств является методом выбоunclassified